The yeast mutant vps5Δ affected in the recycling of Golgi membrane proteins displays an enhanced vacuolar Mg(2+)/H(+) exchange activity - Borrelly, Gilles (National Academy of Sciences, 2001)
Growth of the yeast vacuolar protein-sorting mutant vps5Δ affected in the endosome-to-Golgi retromer complex was more sensitive to Mg(2+)-limiting conditions than was the growth of the wild-type (WT) strain. This sensitivity was enhanced at acidic pH. The vps5Δ strain was also sensitive to Al(3+), known to inhibit Mg(2+) uptake in yeast cells. In contrast, it was found to be resistant to Ni(2+) and Co(2+), two cytotoxic analogs of Mg(2+). Resistance to Ni(2+) did not seem to result from the alteration of plasma-membrane transport properties because mutant and WT cells displayed similar Ni(2+) uptake. After plasma-membrane permeabilization, intracellular Ni(2+) uptake in vps5Δ cells was 3-fold higher than in WT cells, which is consistent with the implication of the vacuole in the observed phenotypes. In reconstituted vacuolar vesicles prepared from vps5Δ, the rates of H(+) exchange with Ni(2+), Co(2+), and Mg(2+) were increased (relative to WT) by 170%, 130%, and 50%, respectively. The rates of H(+) exchange with Ca(2+), Cd(2+), and K(+) were similar in both strains, as were α-mannosidase and H(+)-ATPase activities, and SDS/PAGE patterns of vacuolar proteins. Among 14 other vacuolar protein-sorting mutants tested, only the 8 mutants affected in the recycling of trans-Golgi network membrane proteins shared the same Ni(2+) resistance phenotype as vps5Δ. It is proposed that a trans-Golgi network Mg(2+)/H(+) exchanger, mislocalized to vps5Δ vacuole, could be responsible for the phenotypes observed in vivo and in vitro.